2022
DOI: 10.3390/en15207750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quality of the Housing Environment Using Multi-Criteria Analysis That Includes Energy Efficiency: A Review

Abstract: The quality of the housing environment (HE) is an important issue that has a direct impact on the life of inhabitants. Aiming for quality in residential architecture begins with a well-designed HE, with the designing process being a value that is difficult to evaluate. Nowadays, a well-designed HE takes into account the energy efficiency of a building. An appropriate degree of thermal comfort, which is required by inhabitants, needs to be considered at the design stage. Designers can use building certification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…This is further reinforced by the findings of a study indicating that CPTED correlates with the residents' quality of life in residential environments. This correlation encompasses various factors, including the standard of living spaces, the presence of amenities, the convenience of access, safety, and zones of comfort (Mazur et al, 2022).…”
Section: Cpted Residential Environment and Qolmentioning
confidence: 99%
“…This is further reinforced by the findings of a study indicating that CPTED correlates with the residents' quality of life in residential environments. This correlation encompasses various factors, including the standard of living spaces, the presence of amenities, the convenience of access, safety, and zones of comfort (Mazur et al, 2022).…”
Section: Cpted Residential Environment and Qolmentioning
confidence: 99%
“…As a major energy consumer, the building sector has the opportunity to achieve significant environmental and economic benefits through the implementation of modern technologies and design practices [13]. In particular, these changes are expected in technologies for heating and cooling buildings, which account for 40-50% of the total global final energy demand of buildings [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mazur et al [60] conducted a multi-criteria analysis of five systems that can be used to assess the quality of the HE (Housing Environment) and energy efficiency in temperate climates: (1) Building For Life 12, (2) Home Quality Mark, (3) Housing Quality Indicators, (4) Système D'évaluation de Logements (Sel) and ( 5) NF Habitat-NF Habitat HQE. The results of this analysis showed that it is possible to identify factors that improve the quality of the living environment of HE and to prepare objective systems for its measurement that can be used in practice, e.g., in the design industry, real estate or public administration.…”
Section: Introductionmentioning
confidence: 99%